Performance of an Existing Reinforced Concrete Building Designed in Accordance to Older Indonesian Seismic Code: A Case Study for a Hotel in Kupang, Indonesia - Pamuda Pudjisuryadi; Benjamin Lumantarna; Ryan Setiawan; Christian Handoko (Institute of Research and Community Outreach - Petra Christian University, 2018)
The recent seismic code SNI 1726-2012 is significantly different compared to the older code SNI 1726-2002. The seismic hazard map was significantly changed and the level of maximum considered earthquake was significantly increased. Therefore, buildings designed according to outdated code may not resist the higher demand required by newer code. In this study, seismic performance of Hotel X in Kupang, Indonesia which was designed based on SNI-1726-2002 is investigated. The structure was analyzed using Nonlinear Time History Analysis. The seismic load used was a spectrum consistent ground acceleration generated from El-Centro 18 May 1940 North-South component in accordance to SNI 1726-2012. The results show that Hotel X can resist maximum considered earthquake required by SNI 1726-2012. The maximum drift ratio is 0.81% which is lower than the limit set by FEMA 356-2000 (2%). Plastic hinge damage level is also lower than the allowance in ACMC 2001.